Sweet candy company / Izzurul Ramdan Ramli... [et al.] - Ramli, Izzurul Ramdan; Abd Anim, Khairul Ariffin; Jumat, Nadzirha; Roy, Niar (Faculty of Business Management, Universiti Teknologi MARA, 2013)
The name of Sweety Candy is come because of the product itself. Our product is a candy icing that made from sugar icing. Our candy has good quality and our products can be formed into a variety of forms depending on the needs of customers. We take our raw materials from our supplier Sincere Cake Ingredients which is located in Jalan Lintas, Kepayan. We would like to introduce our product to the peoples of Kota Kinabalu and Sepanggar area since this product is very rare and hard to make. Our shop is located in Sulaman Central and it is a strategic place to open a business royal icing candy. We choose Sulaman Central as our store location for several reasons. One of the factors why we chose Sulaman Central as our store location is because one of our target customers is a student university. Majority of students of the UiTM and UMS live around Sulaman Central. We are targeting students who live near Sulaman Central and nearby to buy our products and make our products as a gifts and cake decorations. We are also targeting people who want to have a wedding and make our products as a gift and give it to the guests as a token of thanks for their attendance to the event. Our products also offer reasonable prices depending with the size, quality and appearance and according to the ability of those who live near Sulaman Central. The people who live around Sulaman Central able to buy our products as people who live around Sulaman Central mostly middle-class people.